2008
DOI: 10.1007/s00428-008-0693-7
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic urothelial cell carcinoma with neuroendocrine differentiation arising in renal pelvis. Report of a case

Abstract: Microcystic urothelial cell carcinoma is a rare variant of urothelial cell carcinoma which occurs in the bladder and, rarely, in the renal pelvis. Neuroendocrine differentiation is uncommon in pure urothelial carcinoma and is more frequently found in neoplasms with glandular differentiation. We report a case of microcystic urothelial cell carcinoma arising in renal pelvis and showing focal neuroendocrine differentiation. A 55-year-old man with a history of non-small cell cancer of the lung presented with abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
4
11
1
Order By: Relevance
“…The CK profiling of the present case indicates that CK5/6 emerges and CK20 disappears during sarcomatous transformation in the sarcomatoid carcinoma of the urinary bladder. High-molecular weight CK and CK5/6 are relatively specifically expressed in transitional cell carcinoma [16,17]. In the present case, high-molecular weight CK was present in both elements, though its expression was stronger in sarcomatoid element than in transitional cell carcinoma element.…”
Section: Discussioncontrasting
confidence: 44%
“…The CK profiling of the present case indicates that CK5/6 emerges and CK20 disappears during sarcomatous transformation in the sarcomatoid carcinoma of the urinary bladder. High-molecular weight CK and CK5/6 are relatively specifically expressed in transitional cell carcinoma [16,17]. In the present case, high-molecular weight CK was present in both elements, though its expression was stronger in sarcomatoid element than in transitional cell carcinoma element.…”
Section: Discussioncontrasting
confidence: 44%
“…Neuroendocrine differentiation was suggested by not only immunohistochemical assay but also neurosecretory granules found in tumor cell cytoplasm by electron microscopy. Rarely, neuroendocrine differentiation is observed in microcystic urothelial cell carcinoma of the renal pelvis 17 . Primary neuroendocrine carcinoma of the kidney may be mimicked by neuroendocrine cancer metastasis as reported in Merkel cell carcinoma metastatic to the kidney 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the report of Pacchioni and associates [6] it would be suggested that on rare occasions microcystic variant of urothelial carcinoma may have neuroendocrine differentiation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pacchioni and associates [6] reported a case of microcystic urothelial cell carcinoma arising in the renal pelvis and showing focal neuroendocrine differentiation. They reported a 55-year-old man with a history of non-small-cell carcinoma of the lung who presented with abdominal pain and haematuria.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation